Survey and Identification of Fungi Associated with Eucalyptus camaldulensis in Modibbo Adama Universiy, Yola - Sanusi Kiri, Audu; Idi, Ahmad; Saifullah Mohammed, Yakubu; Victor Ikani, Onuche (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2025)
Eucalyptus species are valuable for timber, pulp, and essential oil production. A laboratory study was conducted which shows the percentage frequency of the fungal isolates in Modibbo Adama University and was calculated based on the total number of isolates obtained from the four different locations. The results showed varying levels of abundance for the four identified fungal species: Rhizopus nigricans was isolated in 2 out of 14 samples, resulting in a percentage frequency of 14.2%. Aspergillus flavus had the second-highest occurrence, being isolated in 5 out of 14 samples, with a percentage frequency of 35%. Penicillium notatum was the least frequent, isolated in just 1 out of 14 samples, giving a percentage frequency of 7.1%. Aspergillus brasiliensis was the most abundant species, isolated in 6 out of 14 samples, accounting for 42.8% of the total isolates. The results of this study highlight the prevalence of fungal pathogens associated with Eucalyptus camaldulensis in the Modibbo Adama University area. Aspergillus brasiliensis and Aspergillus flavus were the most commonly found fungi, indicating that these species may play a significant role in the degradation of Eucalyptus leaves and other tissues. Rhizopus nigicans and Penicillium notatum were less frequent but still present, suggesting their contribution to the overall fungal biodiversity within the study area. This research demonstrates the need for further investigation into the pathogenicity of these fungi, their potential impact on Eucalyptus trees, and the development of management strategies to mitigate fungal infections.